Biomorphic synthesis of cobalt oxide and ceria microfibers: Their application in diesel soot oxidation - Stegmayer, María Angeles (2020)
CeO2, Co3O4 and mixed Co3O4-CeO2 hollow microfibers were synthesized using cotton as biotemplate by incipient wetness impregnation (one step synthesis). Mixed Co3O4-CeO2 fibers were also prepared by incorporating cobalt onto CeO2 fibers by wet impregnation (sequential synthesis). A thorough characterization by BET, XRD, LRS, XPS, EDX and SEM was conducted to correlate the physical chemistry properties of the fibers with their catalytic performance. Ceria fibers showed a maximum combustion rate at TM = 420 °C. While cobalt fibers were even more active (TM = 365 °C), Co3O4-CeO2 fibers resulted in intermediate activity (TM = 380 °C). The good catalytic performance could be related to chemisorbed labile oxygen species (Oβ).